The Role of Some Mineral Substances in the Nutrition of Primary Class Students (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Sufficient supply of primary school students with micronutrients is of special importance for their growth, mental and physical abilities and other indicators. The article presents the amount of calcium, phosphorus, and magnesium in the daily diet of 7-10-year-old schoolchildren. When assessing the provision of children with micronutrients, identifying and analyzing the above-mentioned indicators is of great scientific and practical importance.